ANALISIS EMISI GAS BUANG PADA MESIN KONVENSIONAL SILINDER TUNGGAL - Bambang Hertomo (Universitas Lambung Mangkurat, 2017)
The transportation sector consisting of cars and motorcycles annually increases, so the resulting exhaust gas keeps increasing. Exhaust gases that pollute the environment consist of CO and unburner HC, this is harmful to the environment. Objective to know the optimum value of CO and HC emissions when using fuel with octane value 88 and 90 with main jet size 72 and 105. What is the optimum change of CO and HC emissions at 4000rpm up to 9000rpm with octane fuel 88 and 90 Constant speed method with engine speed ranging from 4000rpm up to 9000rpm used for exhaust emissions. Results for main jet 72 octane 88 value 3.19% CO, 264,62ppm and optan 90 value 3.09% CO 242,29ppm. For main jet 105 octane 88 value 3.36% CO, 278,62ppm and octane 90 value 252,62ppm HC.